Development of extrusion technology for magnesium alloy ZE20. (2017) - Plumeri, John E.; Madej, Lukasz; Misiolek, Wojciech Z.
Abstract: The development of extrusion technology for a new magnesium alloy ZE20 (2.4 %wt. Zn, 0.2 %wt. Ce) requires evaluation of a model for the alloy's deformation behavior. In this study, compression tests have been carried out for a wide range of temperatures (350-425 °C) and strain rates (0.01-10.0 s -1 ) corresponding to a wide range of extrusion parameters. An inverse analysis was applied to produce accurate true stress-strain data. A Johnson-Cook type flow stress model was selected and flow curves for a wide range of processing conditions have been developed. Friction has a significant influence on thermomechanical process parameters and increases deformation temperature. A comparison with compression test results was performed. This metallurgical knowledge was then applied together with the calibrated ZE20 material model to the design of an industrial direct extrusion process of a customized hollow beam. Both the indirect and direct extrusion processes were designed, numerically simulated, and carried out for development of new numerical DEFORM-3D TM model. It has been demonstrated that the numerical model accurately predicted high-strain plastic flow stress values as compared with experiments for the new alloy as well as strain, strain rate, and temperature values within the formed extrudate.